Pantone the 20th century in color - Eiseman, Leatrice; Recker, Keith
"Pantone, the worldwide color authority, invites you on a rich visual tour of one hundred transformative years. In this comprehensive volume, more than 200 images of iconic art, products, decor, and fashion are carefully matched with official PANTONE matched palettes to reveal the trends, radical shifts, and resurgences of various hues. This is essential resource for anyone seeking a deeper understanding of the importance of color."--